Relationship Between Lack of Motivation for Sports Performance and Exposure to Sports Injuries Among Young Soccer Players in Algeria - Mourad AHMEDI (Social Empowerment Journal, 2024)
A sports injury is an obsession for every player and has a negative impact on their psyche and, therefore, the fear of an injury and its severity reduces the player's performance, and therefore a lot of attention should be paid to attention to the medical aspect, especially to rehabilitation, which must be in accordance with the type of injury. The current study aimed to identify the relationship between poor motivation for sports performance and exposure to sports injuries among young soccer players in Algeria. The study sample consisted of 30 players from the under-19 category who were randomly chosen from clubs in the city of Bou Saada.With a descriptive approach, we used the Achievement Motivation Scale and a special form to control the nature and number of injuries sustained by players.The results indicated that there is a strong correlation between injury recurrence and lack of motivation for sports performance among young soccer players. In addition, there is a correlation between the degree of sensation of physical pain derived from a sports injury and the lack of motivation for sports performance among young soccer players.